Automatically activated stereotypes and differential treatment against the obese in hiring - Dan-Olof Rooth (Institute for the Study of Labor (IZA), 2008)
This study provides empirical support for automatically activated associations inducing unequal treatment against the obese among recruiters in a real-life hiring situation. A field experiment on differential treatment against obese job applicants in hiring is combined with a measure of employers' automatic/implicit performance stereotype toward obese relative to normal weight using the implicit association test. We find a strong and statistically significant obesity difference in the correlation between the automatic stereotype of obese as being less productive and the callback rate for an interview. This suggests that automatic processes may exert a significant impact on employers' hiring decisions, offering new insights into labor market discrimination.
urn:nbn:de:101:1-20081126748
Keywords: J64; 330; Implicit stereotypes; obese job applicants; differential treatment; Personalbeschaffung; Arbeitsmarktdiskriminierung; Gesundheitsrisiko; Feldforschung; Schweden